Analisis Konten Webometrics Pada Repository Universitas Syiah Kuala Dan Universitas Sumatera Utara - Agusta, Aras Satria (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2019)
Introduction. This article is entitled "Analysis of webometrics content in the Syiah Kuala University repository and the University of North Sumatra". The purpose in writing is to look at the quality of institutional repositories based on webometrics content, which has an impact on the ranking of webometrics 2020. Data Collection Method. In this article the authors use a descriptive quantitative approach, while observations are made by observing and analyzing search results on webometrics indicator devices systematically and in a standardized manner. existing indicators, data generated for each webometrics content indicator against size indicators, visibility indicators, rich file indicators, scholar indicators on institutional repository websites through search engines and normalized. Result and Discussions. The results of this study are that each indicator of size, visibility, rich file and scholar in the repository of the University of North Sumatra is superior to Syiah Kuala University with the total ranking of the December 2019 webometrics indicator is 3.56506 while Syiah Kuala University with a total value of 0.83811 . Then the difference in the total rating in the repository is 2.72695, which allows a change in the ranking of the two universities. Conclusions. From the results of the repository ranking, the University of North Sumatra was superior with a score of 3.56506 while Syiah Kuala University with a total score of 0.83811. Then the difference in the total ranking value in the repository is 2,72695 which has an impact on each achievement of activeness with loyal members of the community in developing institutional repositories. From this, the academic community of each campus should encourage their scientific works to be published on the repository website they already have, while students submit their scientific work in the form of a paper or final project to the library and then processed and disseminated on the repository website.